2018
DOI: 10.2147/ijn.s187906
|View full text |Cite
|
Sign up to set email alerts
|

Novel SN38 derivative-based liposome as anticancer prodrug: an in vitro and in vivo study

Abstract: BackgroundMany novel drug delivery systems have been extensively studied to exploit the full therapeutic potential of SN38, which is one of the most potent antitumor analogs of camptothecins (CPTs), whose clinical application is seriously hindered by poor water solubility, low plasmatic stability, and severe toxicity, but results are always unsatisfactory.MethodsIn this study, combining the advantages of prodrug and nanotechnology, a lipophilic prodrug of SN38, SN38-PA, was developed by conjugating palmitic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Liposomes are phospholipid bilayers equipped with inner aqueous pockets that are used as drug delivery enhancers of hydrophobic and hydrophilic agents [ 108 ]. Liposomes provide a protective layer that shelters encapsulated drug from the structural alterations or chemical degradation [ 109 ]. Furthermore, the covalent adherence of polyethylene glycol (PEG) molecules can be used to improve the systemic circulation of drugs [ 110 ].…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…Liposomes are phospholipid bilayers equipped with inner aqueous pockets that are used as drug delivery enhancers of hydrophobic and hydrophilic agents [ 108 ]. Liposomes provide a protective layer that shelters encapsulated drug from the structural alterations or chemical degradation [ 109 ]. Furthermore, the covalent adherence of polyethylene glycol (PEG) molecules can be used to improve the systemic circulation of drugs [ 110 ].…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…In previous pharmacokinetic studies from literature and tumor-bearing mice PK study in the present study, the results showed that the plasma concentration of SN38 which is the major metabolite of CPT-11 gave a log-linear decrease [ 30 ]. CPT-11 has a large CL and theoretical V ss of pharmacokinetic parameter in vivo [ 31 , 32 ]. A large V ss may indicate rapid and extensive uptake into most tissues which may lead to an off-target toxicity for a cancer chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…For IRI delivery, several liposomal formulations have been developed and exhibited superior anticancer potential when compared with the free drug, and many of these formulations encapsulate directly IRI's active metabolite SN-38 [132,149,[156][157][158][159]. For example, Xing et al [149] developed, by the ethanol injection method, stable liposomal carriers of moeixitecan, a lipophilic SN38 prodrug. Their outcomes depicted a superior cytotoxic activity and a significantly increased proapoptotic potential than free IRI and moeixitecan in HT-29 tumor cell cultures.…”
Section: Lipid-based Drug-delivery Systemsmentioning
confidence: 99%